Cervical cancer prevention: perceptions of women attending Knysna primary health care clinics - Visser, Liesl (Stellenbosch : Stellenbosch University, 2017)
ENGLISH SUMMARY : Background: Cervix cancer is the cancer with the highest prevalence and mortality in Africa. The current screening method is by pap-smear, but other methods of screening and primary prevention against human papillomavirus (HPV) by immunization are currently being investigated. The aim of this study was to explore the experience, knowledge, attitude and beliefs of the clinic attending women attending clinics in the Knysna sub-district regarding the current cervical screening programme and to obtain their opinion on the possible alternatives methods available. Method: A prospective quantitative and qualitative study was conducted in six primary health care clinics in the Knysna sub-district. Data was collected from 206 completed questionnaires, by sequentially selected women aged 20-65 years. Six focus group discussions were held. Descriptive results were presented as means for continuous/ordinal data, and percentages for categorical data. The Chi-square test was used to test for relationships, Mann-Whitney and Kruskal-Wallis tests were used to compare groups’ mean values and Spearman correlations for comparison between ordinal variables. A 5% significance level (p<0.05) was used as guideline for determining significant results. The qualitative data was analyzed using the framework approach. Results: One hundred and seventy nine (87%) knew that a pap-smear was to screen for pre-malignant or malignant cells. Seventeen participants (8%) didn’t believe that cervix cancer is preventable by regular pap-smears and 204 (99%) believed that abnormal cells are treatable before it becomes cancer. Hundred and twenty three (60%) didn’t know that different screening programmes exist for HIV positive and negative women. One hundred and forty one (68%) had undergone pap-smears. The result was collected by 115 (82%) of which 108 (77%) reported understanding the meaning. Fourteen(10%) were referred for further treatment, 47 (33%) were requested to return for another smear the subsequent year. Of this collective group, 31 (62%) complied. The Visual Inspection with Acetic acid (VIA) method was acceptable to 153 (74%). HPV DNA-testing was acceptable to 171 (83%). HPV vaccination was acceptable to all participants. The focus groups identified the following themes: knowledge, application, personal esteem, community influence and protection of youth. Conclusion: Participants had a good basic knowledge of pap smears. Uptake of pap-smears were acceptable but the follow-through was incomplete and influential, externally factors were identified. The influence of the community’s opinion on the women’s ideas should not be disregarded. The participants were serious about protecting the youth and felt unable to do so with the current system. Alternative methods of cervix cancer prevention are acceptable to the community in Knysna and should be explored further.